Cross-cultural adaptation and validation of the 9-item Indonesian HIV/AIDS Stigma Scale (InHASS-9) for the general population - Arifin, Bustanul; Alkaff, Firas F.; Salamah, Sovia; Rauf, Saidah; Zulkarnain, Zulkarnain; Noor, Rasuane; Perwitasari, Dyah A.; Padmawati, Retna S.; Alkaff, Sylmina D.; Dwicahya, Bambang; Yuliet, Yuliet; Fajriansyah, Fajriansyah; Postma, Maarten J.; Kurniawan, Muh D.; R. Rokhman, Muhammad (Narra J, 2025)
Stigma against people living with human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) (PLWHA) poses significant health threats and contributes to the uncontrolled transmission of HIV. Although tools for measuring stigma against PLWHA have been validated in Indonesia, a previous study was geographically limited and conducted with small sample sizes. The aim of this study was to perform cross-cultural adaptation and validate the psychometric properties of the 9-item Indonesian HIV/AIDS Stigma Scale (InHASS-9) in the Indonesian general population. Utilizing a cross-sectional design, the study recruited 1,302 participants from six major islands in Indonesia. The validity of the instrument was determined using recognized group validity and construct validity, while internal consistency was evaluated using Cronbach's alpha. During the adaptation phase, nine simple items were finalized for inclusion in the scale. The findings revealed that the InHASS-9 instrument exhibited strong internal consistency, with Cronbach's alpha coefficient of 0.83, indicating high reliability. In conclusion, the InHASS-9 instrument is a valid and reliable tool for assessing the extent of social stigma associated with PLWHA in Indonesia.